Ideologically Selective Pictures of Serbian Culture? (KULT_online, 2009)
Holm Sundhaussen’s 2007 monograph Geschichte Serbiens. 19.-20. Jahrhundert (History of Serbia: 19th through 20th century) follows Serbian history from the first Serbian rebellion under the Ottoman Empire in 1804 until the end of the Milošević era in 2000. He focuses on the area of the earliest autonomous Serbian state and this region within the first and second Yugoslavia. After examining the "long 19th century" (1800-1918), with elucidations of the insurgency, the Kosovo-myth, Serbian enlightenment, language standardisation and Serbia's role in World War I, the bulk of Sundhaussen's work is on the "short 20th century", from the formation of the Kingdom of Serbs, Croats and Slovenes — later known as the Kingdom of Yugoslavia — to World War II and Serbia within the Socialist Federal Republic of Yugoslavia. Of course, the history would not be complete without discussions of Yugoslavia's fall, the civil wars of the 1990s and Serbia's ultimate accountability.